BRAND EQUITY INFLUENCE TOWARD CUSTOMER LOYALTY THROUGH SATISFACTION AT TRIBUN JATENG PENGARUH EKUITAS MEREK TERHADAP LOYALITAS PELANGGAN MELALUI KEPUASAN PADA KORAN TRIBUN JATENG - Wildan Hermawan S; Hari Susanta Nugraha (Jurnal Ilmu Administrasi Bisnis, 2016)
Aims to know the influence between the brand equity to customer loyalty through satisfaction at the Tribun Jateng newspaper. Type of research is explanatory research. Respondents in this study is the Semarang people who've bought the Tribun Jateng as many as 100 people. Data were analyzed using validity and reliability test, t-test, f test, path analysis and Sobel test.Results from this study is the brand equity have a significant effect on customer loyalty with t calculate equal to 8.569, brand equity have a significant effect on customer satisfaction with t amounted to 11.874, satisfaction significantly influence customer loyalty with t calculate equal to 8.322, satisfaction mediate between brand equity and customer loyalty partially, the result of the path analysis amounted to 0,367 direct effect while the indirect effect is 0.275808. From these results it can be seen that the direct effect of brand equity to customer loyalty is greater than its indirect effect, results of the Sobel test, standard error of the magnitude of the indirect effect shows the results of 0.002605611, and found t count equal to 2.8934 larger of t table is 1.98447 thus it can be concluded that (Z) mediates the relationship between (X) and (Y).